Hubungan Tingkat Pengetahuan Penderita Hipertensi Tentang Penyakit Hipertensi Dengan Kepatuhan Regimen Terapeutik Di Kelurahan Lirboyo Rw 03 Dan 08 Kota Kediri - Puguh Santoso (coba, 2015)
In the prevention of complications of hypertension motivated by three factors: predisposing factors include knowledge, attitudes, beliefs, values, family traditions, contributing factors include the availability of source facilities, predisposing factors include attitudes, behaviors of health workers, family and friends. Knowledge or cognition is the dominant factor is very important to person's behavior to obey with the therapeutic regimen. Methods: This study design using analytical observation, while the population in this study are patients with hypertension who are in the Urban Village Lirboyo RW 03 and 08 of Kediri. Sample studies using total sampling, which amounted to 21 respondents. Questionnaires given to obtain in-depth information about the level of knowledge and compliance in hypertensive patients undergoing therapeutic regimen. Results, level of knowledge about hypertension hypertensive patients almost all respondents (71%) good knowledge, compliance majority of respondents (76%) adherence to the therapeutic regimen, a small portion of respondents (24%) are less adherent to the therapeutic regimen. Results of the few respondents knowledgeable enough (29%). Therapeutic regimen research necessary to increase knowledge and necessary also social support, resources, attitudes, behaviors, and motivations of people with hypertension to improve compliance in implementing the therapeutic regimen. Keywords: Knowledge Level, compliance